The Dividend Displacement Property and the Substitution of Anticipated Earnings for Dividends in Equity Valuation - Penman, Stephen H.; Sougiannis, Theodore (The Accounting Review, 1997)
[The paper demonstrates empirically that earnings prepared according to Generally Accepted Accounting Principles (GAAP earnings) have properties necessary to serve as a substitute for dividends in equity valuation analysis. Dividends reduce subsequent GAAP earnings, and "intrinsic" equity prices calculated by forecasting earnings are thus reduced by current dividends. This behavior is in accordance with the Miller and Modigliani principle-the displacement property-which states that the payment of dividends reduces prices, dollar for dollar. Further, the paper demonstrates that if this displacement is accommodated in calculating equity prices from forecasted GAAP earnings, those prices exhibit the dividend irrelevance property, that is, calculated prices are insensitive to future dividends. Forecasted GAAP earnings cannot be substituted for dividends, dollar for dollar, but the two are substitutes in the sense that the replacement value of expected dividends reduces forecasted earnings, dollar for dollar.]